2010
DOI: 10.26419/res.00063.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Romance, and Relationships: AARP Survey of Midlife and Older Adults

Abstract: AARP is a nonprofit, nonpartisan membership organization that helps people 50+ have independence, choice and control in ways that are beneficial and affordable to them and society as a whole. AARP does not endorse candidates for public office or make contributions to either political campaigns or candidates. We produce AARP The Magazine, the definitive voice for 50+ Americans and the world's largest-circulation magazine with over 35.7 million readers; AARP Bulletin, the go-to news source for AARP's millions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 0 publications
4
89
0
Order By: Relevance
“…The majority of aging sexual risk literature focuses solely on condom use, and shows that OA condom use rates are consistently low across gender, race, relationship status, and cohort (Fisher, 2010; Glaude-Hosch et al, 2015; Schick et al, 2010). Using National Survey of Sexual Health and Behavior (NSSHB) data, Schick and others (2010) examined condom use during the most recent sexual encounter among persons 50+ with multiple sexual partners (n = 203).…”
Section: Sexual Risk Among Older Adults In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of aging sexual risk literature focuses solely on condom use, and shows that OA condom use rates are consistently low across gender, race, relationship status, and cohort (Fisher, 2010; Glaude-Hosch et al, 2015; Schick et al, 2010). Using National Survey of Sexual Health and Behavior (NSSHB) data, Schick and others (2010) examined condom use during the most recent sexual encounter among persons 50+ with multiple sexual partners (n = 203).…”
Section: Sexual Risk Among Older Adults In the United Statesmentioning
confidence: 99%
“…Older adult (OA) sexual health deserves attention, as sexual well-being is identified as important to OAs (Fisher, 2010), and sexually transmitted infection (STIs) rates have increased steadily. Approximately 11% of new HIV infections annually in the United States are among adults aged 50+ (Center for Disease Control and Prevention [CDC], 2015).…”
mentioning
confidence: 99%
“…DeLamater and Moorman (2007) found an association between attitudes about sexuality and the frequency of partnered sexual behavior. Research has also found that men are more likely than women to rate sex as important (Fisher, 2010). In a survey of 1,384 persons over age 45, negative attitudes toward sex were significant predictors of low sexual desire among men and women (DeLamater & Sill, 2005), and, apart from age, the effects of attitudes were larger than the effects of other predictors (e.g., illness, medication, having a sexual partner).…”
mentioning
confidence: 97%
“…With the -new‖ generation of older adults, attitudes and beliefs about sex are becoming increasingly more liberal (Schmidt & Mattiesen, 2003;Slagsvold & Strand, 2005;Syme, 2014) and the vast majority of older adults perceive sex as critical for a good relationship and quality of life (Fisher, 2010). In a large Danish sample of adults more than 90% reported that their sex life was of great importance to them and among older adults an inability to maintain a sex life was perceived as a threat to health as great as -complete loss of hearing‖ and -treatment indicated hypertension‖ (Graugaard et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…We also controlled for several additional independent variables that have been included in previous studies of attitudes toward premarital sex (Brewster, Cooksey, Guilkey, & Rindfuss, 1998;Eyal & Kunkel, 2008;Fisher, 2010;Petersen & Donnenwerth, 1997;Petersen & Hyde, 2011;Singh, 1980;Smith, 1997Smith, , 2006Smith, , 2008Weinberg & Williams, 1980;Widmer, Treas, & Newcomb, 1998). We controlled for several sociodemographic characteristics, including sex (sex: female ¼ 1, male ¼ 0), race (binary variables for White [reference], Black, and other race), education (in years), log family income (in logged 1986 dollars), employed (currently employed ¼ 1, else ¼ 0), and being from the South (region: South ¼ 1, else ¼ 0).…”
Section: Variablesmentioning
confidence: 99%